Methodology and fieldwork - Srivastava Vinay Kumar (Oxford OUP, 2005)
This volume contains an account, written by well-known scholars, of the research methods used in social anthropology and sociology. Divided into four parts, the first section touches on the nature of social research; the second discusses fieldwork; the t
Keywords: Ethnology; Sociology; Sociology-fieldwork; Sociology-methodology